Resistencias discursivas de intelectuales de República Dominicana durante la ocupación estadounidense de 1916-1924: nacionalismo, antiimperialismo e hispanismo (Tzintzun, Revista de Estudios Históricos, 2016)
Between 1916 and 1924, the Dominican Republic was under the military occupation of the USA. One of the most visible consequences of the occupation was the start of a civil, pacific, urban resistance by Dominican Intellectual key figures of those years. This article discusses, from the point of view of cultural and intellectual history, certain topics which characterized the discourse, such as Hispanism and Hispano-Americanism, based on which the ideas of nation, identity and otherness were redefined in this Caribbean country during the first decades of the 20th century.
Keywords: Dominican Intellectuals; Nationalist Discourse; Hispanism; Hispano-Americanism; Anti-imperialism